2012
DOI: 10.1037/a0029925
|View full text |Cite
|
Sign up to set email alerts
|

Late onset of age-related difference in unpaced tapping with no age-related difference in phase-shift error detection and correction.

Abstract: An age-related difference in accuracy and variability of unpaced timing tasks suggests that the internal clock for the processing of intervals of hundreds of milliseconds slows down with age. However, we recently found that sensorimotor synchronization (SMS) error detection and correction abilities are preserved into the ninth and tenth decades, although fastest tapping rate decreases (Turgeon, Wing, & Taylor, 2011). Further testing with the same sample of participants in the present study provides evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 56 publications
3
62
1
Order By: Relevance
“…In beat tempi between 300 and 700 ms, age‐related differences were visible only during continuation tapping (Woodruff‐Pak & Jaeger, ; Vanneste et al ., ). Increasing age was associated with more variable tapping rates (Turgeon & Wing, ), and this was most likely caused by variability of internal timing, rather than a motor component. Reduced variability in both central timekeeping and motor implementation has been reported for expert pianists (Krampe et al ., ; Iannarilli et al ., ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In beat tempi between 300 and 700 ms, age‐related differences were visible only during continuation tapping (Woodruff‐Pak & Jaeger, ; Vanneste et al ., ). Increasing age was associated with more variable tapping rates (Turgeon & Wing, ), and this was most likely caused by variability of internal timing, rather than a motor component. Reduced variability in both central timekeeping and motor implementation has been reported for expert pianists (Krampe et al ., ; Iannarilli et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…However, it is difficult to relate these findings to our first observation as there is no single and task‐independent effect of ageing on beta oscillations. Also, the weak signal at the fast stimulus rate might be related to ‘age‐related slowing’, which has been observed in tapping spontaneously at individuals’ preferred rate, as well as in the fastest tapping rate that individuals could perform (McAuley et al ., ; Turgeon & Wing, ). Their findings point towards the deterioration of the internal clock representation again; however, they do not directly rely on the measured variability, but on the absolute slowing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggest that behaviors driven by endogenous dynamics are more suitable to reflect the true state of the internal clock (e.g., its speed) . In a more recent study, Turgeon and Wing observed that aging (they tested participants up to 98 years old, which is a relatively higher age range compared to previous studies) was associated with a slower rate of tapping as well as higher timing variability in a variety of unpaced tapping tasks (see Refs. and for consistent results regarding temporal imprecision), which were attributed to the noise in the timing system (e.g., instead of sensorimotor noise).…”
Section: Temporal Processing Of Healthy Agingmentioning
confidence: 97%
“…Additionally, the observed age difference disappeared in synchronization tasks even after the external timing cues that the participants could entrain to were terminated. This was presumably due to the correction of timing of responses with external cues, which highlights feedback as another important methodological factor that needs to be kept in mind, as well as intact error detection and correction mechanisms in aging . The results of Vanneste et al .…”
Section: Temporal Processing Of Healthy Agingmentioning
confidence: 97%